ТРАНСФОРМАЦІЯ ФІНАНСОВОЇ ЗВІТНОСТІ В УМОВАХ ПАНДЕМІЇ COVID-19 - Миськів, Любов; Безручук, Світлана (SWorldJournal, 2022)
The 21st century has posed new challenges to both Ukraine (due to the hybrid war) and the world (due to the Crown Virus pandemic (COVID-19)). First of all, this has affected the financial reporting of many companies around the world since the first quart